2006
DOI: 10.1021/ja0656604
|View full text |Cite
|
Sign up to set email alerts
|

Rotational-Echo Double-Resonance NMR Distance Measurements for the Tubulin-Bound Paclitaxel Conformation

Abstract: The important anticancer drug Taxol ® (paclitaxel, PTX) owes its unique activity to its ability to bind to tubulin in a stoichiometric ratio and promote its assembly into microtubules. The conformation of the microtubule-bound drug has been the focus of numerous research efforts, since the inability of polymerized tubulin to form crystals precludes structure proof by X-ray crystallography. Likewise, although the αβ-tubulin dimer structure has been solved by electron crystallography, the 3.7 Å resolution is too… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
88
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 73 publications
(96 citation statements)
references
References 54 publications
(113 reference statements)
7
88
0
Order By: Relevance
“…the distances between the fluorine on the C2 benzoyl group and the labeled side chain carbons were determined to be 9.8 and 10.3 Å (Figure 3; Li et al, 2000). This result has been extended by some recent results with the labeled analog 23; these results indicated a distance of 6.3 Å between the p-fluorine on the C3′-phenyl and the methyl protons of the C4-acetate (Paik et al, 2007). These data are fully consistent with the T-taxol hypothesis, which has a particularly short C3′-phenyl to C4-acetate distance (Figure 4) The REDOR NMR studies described above gave strong support for the T-Taxol conformation as being the best descriptor of the tubulin-binding form of taxol.…”
Section: The Interaction Of Taxol With Tubulinsupporting
confidence: 56%
“…the distances between the fluorine on the C2 benzoyl group and the labeled side chain carbons were determined to be 9.8 and 10.3 Å (Figure 3; Li et al, 2000). This result has been extended by some recent results with the labeled analog 23; these results indicated a distance of 6.3 Å between the p-fluorine on the C3′-phenyl and the methyl protons of the C4-acetate (Paik et al, 2007). These data are fully consistent with the T-taxol hypothesis, which has a particularly short C3′-phenyl to C4-acetate distance (Figure 4) The REDOR NMR studies described above gave strong support for the T-Taxol conformation as being the best descriptor of the tubulin-binding form of taxol.…”
Section: The Interaction Of Taxol With Tubulinsupporting
confidence: 56%
“…As a result, the intensity of the echo signal, S, measured in the presence of the recoupling pulse is smaller than that of S 0 measured in its absence. The fractional signal reduction (S 0 − S)/S 0 , called the REAPDOR fraction, is a function of the size of the dipolar coupling constant D and, hence, of the internuclear distance r through the relationship (1) where D is expressed in units of Hz and γ S and γ I are the magnetogyric ratios of the quadrupolar and observed nuclei, respectively. In practical applications the REAPDOR fraction is measured as a function of the evolution time τ between the excitation pulse and the beginning of the data acquisition ( Figure 1).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…[1][2][3][4] Internuclear distances in solid-state NMR are derived from the dipolar interaction. The strength of the dipolar interaction depends on the magnetogyric ratios of the nuclei as well as on the inverse cube of the internuclear distance, r −3 , thus providing a direct distance probe.…”
Section: Introductionmentioning
confidence: 99%
“…The main difference between this conformer (named REDOR-taxol or PTX-NY) and T-taxol is the conformation of the C13 side chain, that places the 2 ¢ -OH in a different orientation. However, subsequent studies demonstrated that PTX-NY is not consistent with the EC density [86,87] .…”
mentioning
confidence: 95%